Functional characterization of the halogenase SpmH and discovery of new deschloro-tryptophan dimers. Issue 5 (13th December 2018) - Liu, Zhiwen; Ma, Liang; Zhang, Liping; Zhang, Wenjun; Zhu, Yiguang; Chen, Yuchan; Zhang, Weimin; Zhang, Changsheng
Abstract : Inactivation of the halogenase gene spmH led to discovery of four new deschloro-tryptophan dimers. SpmH was further biochemically characterized in vitro as anl -tryptophan 5-halogenase. Abstract : The halogenase gene spmH was putatively involved in the biosynthesis of spiroindimicins/indimicins (SPMs/IDMs), a group of chlorinated tryptophan dimers (TDs) from deep-sea-derived Streptomyces sp. SCSIO 03032. Inactivation of spmH led to six deschloro-analogues of TDs, including four new compounds SPMs G (1 ) and H (2 ), and IDMs F (3 ) and G (4 ). The structures and absolute configurations of1–4 were unambiguously determined by the combination of extensive spectroscopic analysis, single-crystal X-ray diffraction and quantum chemical ECD calculations. Compounds1 and2 exhibited moderate cytotoxic activities against four cancer cell lines. Additionally, SpmH was biochemically characterized in vitro as anl -tryptophan 5-halogenase.